2016
DOI: 10.1039/c6tb01154c
|View full text |Cite
|
Sign up to set email alerts
|

Photocrosslinkable chitosan hydrogels functionalized with the RGD peptide and phosphoserine to enhance osteogenesis

Abstract: Hydrogels derived from naturally occurring polymers are attractive matrix for tissue engineering. Here, we report a biofunctional hydrogel for specific use in bone regeneration by introducing Arg-Gly-Asp (RGD)-containing cell adhesive motifs and phosphorylated serine residues, which are prevalent in native bone extracellular matrix and known to promote osteogenesis by enhancing cell-matrix interactions and hydroxyapatite nucleation, into photopolymerizable methacrylated glycol chitosan (MeGC). Incorporation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
109
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 77 publications
(112 citation statements)
references
References 39 publications
(41 reference statements)
2
109
0
1
Order By: Relevance
“…We have previously developed an injectable hydrogel system composed of visible light crosslinkable chitosan (methacrylated glycol chitosan, MeGC) and riboflavin as a photoinitiator [3638]. The MeGC hydrogel well supported proliferation of encapsulated MSCs and their commitment to an osteo- and chondroprogenitor lineage[3840].…”
Section: Introductionmentioning
confidence: 99%
“…We have previously developed an injectable hydrogel system composed of visible light crosslinkable chitosan (methacrylated glycol chitosan, MeGC) and riboflavin as a photoinitiator [3638]. The MeGC hydrogel well supported proliferation of encapsulated MSCs and their commitment to an osteo- and chondroprogenitor lineage[3840].…”
Section: Introductionmentioning
confidence: 99%
“…RGD, derived from fibronectin, is the most investigated peptide. The peptide can build a bridge between cell receptor and surface and subsequently improve cell adhesion, differentiation and proliferation as well as cell survival on, various substrate surfaces [28][29][30][31]. Our studies showed that the incorporation of RGD in multi-drug loaded polypeptide nanofilms indeed led to significantly improved cell adhesion (Figures 3, 4A and 4B), proliferation ( Figure 4C), and viability ( Figure 5).…”
Section: Discussionmentioning
confidence: 74%
“…The solution was mixed homogeneously, lyophilized overnight, and then redispersed in 285 μL of DMSO. For E2/ND/G synthesis, methacrylated glycol chitosan (MGC) was prepared as described previously (69). The E2/ND was mixed homogenously with MGC in 1 mL water (ND: E2: polymer = 5 mg: 2.1 mg: 20 mg) followed by overnight lyophilization.…”
Section: Methodsmentioning
confidence: 99%